Evaluasi Pelaksanaan Program Posbindu PTM di Puskesmas Kota Wilayah Utara Kota Kediri - Reny Nugraheni; Richa Chintya; Tri Cahyono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
One of the problems faced in health development today is the shift in disease patterns from communicable to non-communicable diseases. A report from WHO shows that PTM is by far the leading cause of death in the world, representing 63% of all annual deaths. This study aims to evaluate the implementation of the Posbindu PTM program in the North Regional Health Center of Kediri City. This research method was descriptive qualitative method. The informants in this study were the holders of the Posbindu PTM program. The technique of determining this informant was using purposive sampling technique. Primary data collection techniques by means of interviews and secondary data collection by document study. There were constraints in the input section, namely the implementation method, namely the passive method since the Covid-19 pandemic was not carried out and there was no special scheduling when the mobile screening was carried out. While the results of the Posbindu PTM implementation process, there were obstacles during the mobile screening, namely that there were residents who did not carry ID cards. And the output of the Puskesmas had not yet reached 50%. The conclusions that can be drawn from this research are the components of input, process, and output of the implementation of the Posbindu PTM program, there are still deficiencies that make the implementation of the program not optimal.Keywords: evaluation; input; process; output; Posbindu PTM ABSTRAK Salah satu masalah yang dihadapi dalam pembangunan kesehatan saat ini adalah terjadinya pergeseran pola penyakit dari penyakit menular ke penyakit tidak menular. Laporan dari WHO menunjukkan bahwa PTM sejauh ini merupakan penyebab utama kematian di dunia, yang mewakili 63% dari semua kematian tahunan. Penelitian ini bertujuan untuk mengevaluasi pelaksanaan program Posbindu PTM di Puskesmas Kota Wilayah Utara Kota Kediri. Metode penelitian ini adalah dengan metode kualitatif deskriptif. Informan dalam penelitian ini adalah pemegang program Posbindu PTM. Teknik dalam penentuan informan ini menggunakan teknik purposive sampling. Teknik pengumpulan data primer dengan cara wawancara dan pengumpulan data sekunder dengan studi dokumen. Terdapat kendala pada bagian input yaitu pada metode pelaksanaan yaitu metode pasif semenjak ada pandemi covid-19 tidak terlaksana serta waktu mobile skrining belum terdapat penjadwalan khusus. Sedangkan hasil dari proses pelaksanaan Posbindu PTM terdapat kendala pada saat mobile skrining yaitu terdapat warga tidak membawa KTP. Dan untuk outputnya Puskesmas belum dapat mencapai 50%. Simpulan yang dapat diambil dari penelitian ini adalah komponen input, proses, dan output dari pelaksanaan program Posbindu PTM masih terdapat kekurangan yang membuat pelaksanaan program berjalan tidak maksimal.Kata kunci: evaluasi; input; proses; output; Posbindu PTM